Shear behavior of ultra-high-performance reinforced concrete beams – Finite element and uncertainty quantification study. (January 2023) - M. Abbas, Yassir
Abstract: This study examines the safety and the model uncertainty of the ACI 318, ACI -PRC 239/ ACI 544, and JSCE/KCI design codes in terms of their shear strength model for UHPC beams. Structural reliability and finite element analyses were employed to achieve this objective. The FE model developed in this study could accurately predict the shear behavior of nine UHPC beams selected from three different previous kinds of research tested up to their failure loads. The numerical model provided a mean test-to-prediction value of 99.4% with a coefficient of variance of 2.3%. Moreover, the design models for ACI 318 and ACI -PRC 239/ ACI 544 consistently underestimated the shear capacity of UHPC beams. For these design codes, the predicted-to-tested values ranged from 1.4 to 12.8 and 1.1 to 5.7, respectively. In comparison with the ACI 318 code, the ACI -PRC 239/ ACI 544 model had less variability and produced more accurate results. The JSCE/KCI model predicted the UHPC shear capacity of the UHPC beams more precisely than the ACI models, showing an observed-to-calculated mean value of 1.49. The reason for this superiority was attributed to consideration of the JSCE/KCI model for the fiber–matrix interactions of the UHPC. Using ACI 318 and ACI -PRC 239/ ACI 544, it was expected that the relevant reliability indices would have relative values. However, these design codes yielded an index of reliability for the shear strength of UHPC beams that was slightly below the target value of 4.15, thereby presenting a safety issue. However, it was expected that greater safety could be achieved using the JSCE/KCI.